Quark production in heavy ion collisions I: formalism and boost invariant fermionic light-cone mode functions - Gelis, François; Tanji, Naoto (Journal of high energy physics, 2016)
We revisit the problem of quark production in high energy heavy ion collisions, at leading order in $α_s$ in the color glass condensate framework. In this first paper, we setup the formalism and express the quark spectrum in terms of a set of mode functions of the Dirac equation. We determine analytically their initial value in the Fock-Schwinger gauge on a proper time surface $Q_sτ_0\ll 1$, in a basis which makes manifest the boost invariance properties of this problem. We also describe a statistical algorithm to perform the sampling of the mode functions.
Gesehen am 02.06.2020